Relationship of Time and Serum Concentrations of Russell's Viper Venom with Blood Coagulating Factors and Renal Hemodynamics in Anesthetized Dogs Injected with Russell' S Viper Venom and the Effect of Dopamine Plus Furosemide - Thamaree, Sopit; Sitprija, Visit; Hamvivatvong, Orawadee; Thawom, Nongnuch (Journal of Basic and Applied Pharmacology, 2015)
The relationship of time and serum concentrations of Russell's viper venom (RVV), as well as blood coagulating factors, hemodynamics, and renal hemodynamics were studied, in comparison with the co-administration of dopamine plus furosemide, in anesthetized male mongrel dogs (N=18), weighing 10-15 kg. Intravenous infusion of normal saline solution (NSS) containing inulin and para-aminohippuric acid (PAH) was given for renal hemodynamic studies. Twelve dogs were intramuscularly injected with RVV (0.1 mg/kg). Six of these dogs were given with RVV (0.1 mg/kg) followed by infusion of dopamine (D, 3 μg/kg/min) plus furosemide (F, a bolus dose of 1 mg/kg and infusion of 1 mg/kg/h). The other 6 dogs were injected with NSS and served as a control group. Blood and urine samples collected at time 0, 2,6,12 and 24 hour were analysed for inulin, PAH, electrolytes, complete blood count (CBC) and blood coagulating factors including fibrinogen, factor V, factor X and fibrin degradation product (FDP). Calculation were made to obtain renal blood flow (RBF), glomerular filtration rate (GFR), renal vascular resistance (RVR), filtration fraction (FF), fractional excretion (FE) of electrolytes. Serum concentrations of RVV, in twelve dogs given with RVV, were measured by ELISA at time 0, 15 min, 30 min, 1,2,4,6,9,12 and 24 hour. The serum concentrations of RVV were plotted against time on semi-log paper. Kinetic parameters were calculated from the graphs. When comparing the group given with RVV alone and the group given with RVV plus D and F, the results showed gradual absorption of RVV from the injection site into systemic circulation with time of maximum absorption (Tmax) of 9 hours. In both groups, maximum concentration (Cm) of 13.0 ± 13.34 ng/ml and 13.0 ± 2.83 ng/ml, elimination half-life (T1/2 of 26.0 ± 18.53 hours and 16.4 ±10.96 hours, the elimination rate constant (Ke) of 0.0267 ± 0.01 94 h-1 and 0.0423 ± 0.0211 h-1 and volume of distribution (Vd) of 5.56 ± 3.23 I/kg and 6.06 ± 3.85 I/kg, were observed, respectively. Mean arterial blood pressure (MABP) was significantly decreased at time 12 and 24 hours after RVV injection, but slightly decreased in the group given with RVV+D+F. Heart rate was increased owing to sympathetic stimulation as a compensatory mechanism. In the group given with RVV, RBF, GFR, urine flow rate (V) were markedly decreased throughout the period of 24 hours of experiment whereas RVR was significantly increased. In contrary, D plus F could restore the renal function that being altered by RVV. The increase of FF and FEK and the decrease of FENa and FECl were not significant. Among blood components, there was no significant difference among the 3 groups. Blood cell components were slightly increased. Blood coagulating factors, including fibrinogen, factor V, and factor X, were significantly decreased where as FDP was increased throughout the experiment. Dopamine plus furosemide seemed to attenuate the effect of RVV on blood coagulation. These results indicated the failure of blood coagulation induced by RVV. The effects of RVV were closely related to serum RVV concentrations. Binding of RVV to some tissues may be responsible for high apparent Vd and long T1/2, thus duration of RVV action is prolonged. Dopamine plus furosemide synergistically improved the renal functions, thus increased renal clearance of RVV. This may result in lesser effects on blood coagulation. This should be taken into an account when human victims of Russell's viper bites are treated. The conventional treatment using antivenom and maintenance of adequate volume should be monitored and observed over a longer period of time than 24 hours. Dopamine plus furosemide may considerably be useful in treatment of the viper bites.